Thermal Ablation of Benign Thyroid Nodules and Papillary Thyroid Microcarcinoma - Bo, Xiao-Wan; Lu, Feng; Xu, Hui-Xiong; Sun, Li-Ping; Zhang, Kun (Frontiers in Oncology, 2020)
Due to the increasing rates of physical examination and application of advanced ultrasound machines, incidences of benign thyroid nodules (BTNs) and papillary thyroid microcarcinoma (PTMC) were dramatically up-regulated in recent years. Thermal ablation (TA) has been widely used and regarded as a safe and effective method to eliminate or reduce BTNs and recurrent low-risk PTMC. However, conclusions using TA to treat primary PTMC are controversial. Recently, several long-term and prospective studies on TA treatment of BTNs and primary PTMC have been reported. Here, we review current literatures and progress on TA treatment of BTNs and PTMC and underline the way to get the best treatment outcomes, providing a comprehensive insight into the research progresses in this field.